Nieśmiertelność kosmiczna. Na marginesie powieści Tomasza Manna Wyznania hochsztaplera Feliksa Krulla - Ziemiński, Ireneusz (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2012)
This article presents a philosophical interpretation of Thomas Mann’s novel Confessions of Felix Krull, in which the writer presents a very original conception of immortality. According to the main character of the novel, Felix Krull, it is not possible for humans to live after death, but people are, after all, eternal beings, because their existence cannot be eliminated from the history of the world. This means that even if the world ceases to exist in the future, the fact of our existence will remain for eternity because it will always be true that we were once a part of the world and its history.